Physical and Functional Interactions between ELL2 and RB in the Suppression of Prostate Cancer Cell Proliferation, Migration, and Invasion - Xiaonan Qiu (Neoplasia: An International Journal for Oncology Research, 2017)
Elongation factor, RNA polymerase II, 2 (ELL2) is expressed and regulated by androgens in the prostate. ELL2 and ELL-associated factor 2 (EAF2) form a stable complex, and their orthologs in Caenorhabditis elegans appear to be functionally similar. In C. elegans, the EAF2 ortholog eaf-1 was reported to interact with the retinoblastoma (RB) pathway to control development and fertility in worms. Because RB loss is frequent in prostate cancer, ELL2 interaction with RB might be important for prostate homeostasis. The present study explored physical and functional interaction of ELL2 with RB in prostate cancer. ELL2 expression in human prostate cancer specimens was detected using quantitative polymerase chain reaction coupled with laser capture microdissection. Co-immunoprecipitation coupled with deletion mutagenesis was used to determine ELL2 association with RB. Functional interaction between ELL2 and RB was tested using siRNA knockdown, BrdU incorporation, Transwell, and/or invasion assays in LNCaP, C4-2, and 22Rv1 prostate cancer cells. ELL2 expression was downregulated in high–Gleason score prostate cancer specimens. ELL2 could be bound and stabilized by RB, and this interaction was mediated through the N-terminus of ELL2 and the C-terminus of RB. Concurrent siRNA knockdown of ELL2 and RB enhanced cell proliferation, migration, and invasion as compared to knockdown of ELL2 or RB alone in prostate cancer cells. ELL2 and RB can interact physically and functionally to suppress prostate cancer progression.